2012
DOI: 10.3329/bjms.v11i3.11722
|View full text |Cite
|
Sign up to set email alerts
|

Appendicitis- Histology Specific Incidence Trends In A Semi Urban Population In New Delhi: A Study Of 262 Cases

Abstract: Objectives: Acute appendicitis is a condition characterized by inflammation of the appendix for which timely surgery is mandatory to prevent morbidity and mortality. The aim of this study was to assess the differences in incidences, age, sex and seasonal variations and to review the histological diagnoses of all the appendicectomy samples.Methods: A retrospective analysis of patients who underwent appendicectomy at the Hakeem Abdul Hameed Centenary Hospital, New Delhi during the period Jan 2007 to Oct 2010.All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
2
1
Order By: Relevance
“…3,19 Timely surgery is mandatory to prevent this outcome. 15 Perforation rate observed in this study was considerably high compared to the other studies which ranged from 0.8% to 20%. 3-5, 10,11 However, a significant perforation rate (34%) was also found by Chamisa et al 2 Considering the age group, perforated appendicitis peaked in the 0 to 9 years group in our study as shown by Sulu et al 3 Besides in the early ages, the literature also stated that perforation is prevalent in the elderly group.…”
Section: 17contrasting
confidence: 35%
See 2 more Smart Citations
“…3,19 Timely surgery is mandatory to prevent this outcome. 15 Perforation rate observed in this study was considerably high compared to the other studies which ranged from 0.8% to 20%. 3-5, 10,11 However, a significant perforation rate (34%) was also found by Chamisa et al 2 Considering the age group, perforated appendicitis peaked in the 0 to 9 years group in our study as shown by Sulu et al 3 Besides in the early ages, the literature also stated that perforation is prevalent in the elderly group.…”
Section: 17contrasting
confidence: 35%
“…It shows extensive mucosal ulceration and hemorrhage necrosis of all layers under the microscope. 4,15 This grouping of acute appendicitis, however, was not applied in our study site at the time of this study was conducted. The histopathologic type of appendicitis was defined as acute and chronic only.…”
Section: 7mentioning
confidence: 99%
See 1 more Smart Citation